Evaluation of a numerical method to predict the polyphenol content in monovarietal olive oils - Matos, Luís C. (2007)
Three monovarietal virgin olive oils obtained from olives grown under biological agricultural system, in Portugal, with different ripening stages, were studied in what concerns the parameters usually related with oxidation status (total polyphenols, tocopherols, chlorophylls and carotenoids, peroxide values, oxidative stability, specific extinction coefficients K232 and K270 and titratable acidity). A total of 18 samples were analyzed: seven from Cv. Cobranc¸osa (maturation indices 1–7), five from Cv. Madural (maturation indices 3–7) and six from Cv. Verdeal Transmontana (maturation indices 1–6). Oxidative stability and polyphenols profile presented high correlation coef- ficients. Given this high correlation, a numerical method was developed and evaluated to predict total polyphenols contents in olive oil. The method is based on the kinetic equation of the oxidation process in the presence of antioxidants and on Rancimat profiles. Total polyphenols contents obtained with this method were similar to those obtained by the Folin-Ciocalteau method.